Client-Initiated Violence Against Zambian Female Sex Workers: Prevalence and Associations With Behavior, Environment, and Sexual History - Malama, Kalonde; Sagaon-Teyssier, Luis; Parker, Rachel; Tichacek, Amanda; Sharkey, Tyronza; Kilembe, William; Inambao, Mubiana; Price, Matt A.; Spire, Bruno; Allen, Susan (Journal of interpersonal violence, 2021)
Violence against women is a known risk factor for HIV and affects female sex workers (FSW) in sub-Saharan Africa. Little is known about the magnitude and determinants of violence against FSW in Zambia, where HIV and gender-based violence prevalence are high. We conducted a cross-sectional study, using multivariable logistic regression, to determine the prevalence and correlates of client-initiated physical violence among 419 FSW in Lusaka and Ndola. The prevalence of client-initiated physical violence was 39%. The odds of violence were higher for FSW who: lived in Lusaka, recruited clients from the street, serviced clients in the clients’ homes, had a physically forced sexual debut, and had a higher client volume. Our results call for safer working spaces for FSW and violence prevention interventions for their male clients.